2011
DOI: 10.1021/jm200334c
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Steric Space at the Floor of the D1 Dopamine Receptor Orthosteric Binding Domain: 7α-, 7β-, 8α-, and 8β-Methyl Substituted Dihydrexidine Analogues

Abstract: To probe the space at the floor of the orthosteric ligand binding site in the dopamine D1 receptor, four methylated analogs of dihydrexidine (DHX) were synthesized with substitutions at the 7 and 8 positions. The 8α-axial, 8β-equatorial and 7α-equatorial were synthesized by photochemical cyclization of appropriately substituted N-benzoyl enamines, the 7β-axial analog was prepared by an intramolecular Henry reaction. All of the methylated analogs displayed losses in affinity when compared to DHX (20 nM): 8β-Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…Investigations have shown that more negative values propose system spontaneity, and, consequently, improved stability of the complex (Wiggers et al, 2011). These findings are in agreement with experimental data obtained by Cueva et al (2011) who observed a more stable inhibition constant for the complex at 20 nM, as well as hydrogen bonds occurring between the ligant and D 1 receptor through the residues of SER198, ASP103, ASN292 and aromatic interaction between PHE288 and PHE203 with the ligant. Then, molecular docking also showed amino acid residues that promote direct interaction between Cas X and tested receptors.…”
Section: Discussionsupporting
confidence: 89%
“…Investigations have shown that more negative values propose system spontaneity, and, consequently, improved stability of the complex (Wiggers et al, 2011). These findings are in agreement with experimental data obtained by Cueva et al (2011) who observed a more stable inhibition constant for the complex at 20 nM, as well as hydrogen bonds occurring between the ligant and D 1 receptor through the residues of SER198, ASP103, ASN292 and aromatic interaction between PHE288 and PHE203 with the ligant. Then, molecular docking also showed amino acid residues that promote direct interaction between Cas X and tested receptors.…”
Section: Discussionsupporting
confidence: 89%
“…2-Benzoylbenzoic acid derivatives are important intermediates for the synthesis of various bioactive compounds and are often encountered as subunits of many biologically active compounds, including natural products, pharmaceuticals, and agrochemical compounds. For example, balanol, a fungal metabolite produced by the fungus Verticillium balanoides and other fungi, is a potent inhibitor of protein kinase C (PKC), , narceine, an opium alkaloid produced by the Papaver somniferum plant, is a bitter compound with narcotic effects, and pitofenone, the key ingredient in Spasmalgon (a combined drug), is an antispasmodic (Figure ) .…”
mentioning
confidence: 99%
“…80 As a continuation of the SAR pertaining to the D 1 agonist 8, four methyl-substituted analogs were synthesized with substitutions at the 7-and 8-positions (53−56, Figure 4) through strategies involving photochemical cyclization or the intramolecular Henry reaction. 81 However, all of the methylated analogs 53−56 displayed only moderate or low D 1 affinity (270 nM to 10.0 μM). Molecular modeling studies suggested that disruption of an aromatic interaction between Phe203 5.47 and Phe288 6.51 is likely the cause of the 14-fold loss in affinity associated with 8β-axial substitution (53), whereas unfavorable steric interactions with Ser107 3.36 may be responsible for the even more dramatic decreases in D 1 binding affinity suffered by analogs 54−56.…”
Section: Receptor-selective Ligandsmentioning
confidence: 99%
“…As a continuation of the SAR pertaining to the D 1 agonist 8 , four methyl-substituted analogs were synthesized with substitutions at the 7- and 8-positions ( 53 – 56 , Figure ) through strategies involving photochemical cyclization or the intramolecular Henry reaction . However, all of the methylated analogs 53 – 56 displayed only moderate or low D 1 affinity (270 nM to 10.0 μM).…”
Section: Development Of Dopamine Receptor Subtype Ligands: Recent Pro...mentioning
confidence: 99%